Biofuel potential of the newly isolated microalgae Acutodesmus dimorphus under temperature induced oxidative stress conditions. (March 2015) - Chokshi, Kaumeel; Pancha, Imran; Trivedi, Khanjan; George, Basil; Maurya, Rahulkumar; Ghosh, Arup; Mishra, Sandhya
Graphical abstract: Highlights: Acutodesmus dimorphus grows better at 35 °C than at 25 °C cultivation temperature. A. dimorphus accumulated 22.7% lipid, 33.7% carbohydrate and 38% protein at 35 °C. Less oxidative stress was observed at 35 °C compared to 25 °C and 38 °C grown cultures. A. dimorphus can be used as a potential feedstock for biofuel production. Abstract: Lack of control over temperature is one of the major issues in large scale cultivation of microalgae. Therefore, it is important to evaluate the effects of cultivation temperature on the growth and physiology of microalgae. In the present study, freshwater microalgae Acutodesmus dimorphus was grown at different temperature in continuous and two stage cultivation. Results revealed that during continuous cultivation A. dimorphus grows better at 35 °C than at 25 °C and 38 °C. At 35 °C, A. dimorphus produced 22.7% lipid (containing 59% neutral lipid) and 33.7% carbohydrate along with 68% increase in biomass productivity (23.53 mg/L/day) compared to 25 °C grown culture. Stress biomarkers like reactive oxygen species, antioxidant enzymes like catalase and ascorbate peroxidase and lipid peroxidation were also lowest in 35 °C grown culture which reveals that A. dimorphus is well acclimatized at 35 °C.